2005
DOI: 10.1243/135065005x9835
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic analysis of double-layered journal bearings lubricated with couple-stress fluids

Abstract: Elastohydrodynamic (EHD) analysis of a journal bearing with a realistic model for the bearing made of two distinct layers is extended to include couple-stress effects in lubricants blended with polymer additives. Based on the Stokes microcontinuum theory, a transient pressure differential equation (modified Reynolds' equation) is derived from the fluid motion equations and solved numerically. The elegant and powerful semi-analytical approach based on the complex variable theory developed in an earlier work is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
0
22
0
3
Order By: Relevance
“…It was found that the combined effects of couple stress and surface roughness can improve the load carrying capacity and decrease the attitude angle and friction parameters. Recently, Lahmar [17] studied the elastohydrodynamic analysis of double-layered journal bearings based on the Stokes microcontinuum theory. He found that the lubricants with couple stress would increase the load carrying capacity and stability and decrease the friction factor and the attitude angle.…”
Section: Nomenclature Bmentioning
confidence: 99%
“…It was found that the combined effects of couple stress and surface roughness can improve the load carrying capacity and decrease the attitude angle and friction parameters. Recently, Lahmar [17] studied the elastohydrodynamic analysis of double-layered journal bearings based on the Stokes microcontinuum theory. He found that the lubricants with couple stress would increase the load carrying capacity and stability and decrease the friction factor and the attitude angle.…”
Section: Nomenclature Bmentioning
confidence: 99%
“…In 2003, Hsu et al [10] investigated the effects of surface roughness on the dynamic response of short journal bearings lubricated with a couple stress fluid and showed that the combined effects of the couple stress and the surface roughness improved the load-carrying capacity of the journal bearing system and reduced both the rotor attitude angle and the values of the friction factors. In a recent study, Lahmar [11] conducted an elastohydrodynamic analysis of double-layered journal bearings and demonstrated that the use of a couple-stress lubricant increased the load-carrying capacity and stability of the bearing system and reduced the friction effects and attitude angle of the rotor. There are some prominent literatures about non-linear dynamics of rotor-bearing systems.…”
Section: Introductionmentioning
confidence: 99%
“…The new material constant  is responsible for couple-stress property. In the literature, the effects of couple-stresses on the behavior of journal bearings are studied by defining the dimensionless Owing to its relative mathematical simplicity, the couple-stress fluid model has been widely applied to analyze various hydrodynamic lubrication problems: hydrostatic thrust bearings, slider bearings, rolling bearings, squeeze film bearings, layered journal bearings, and dynamically loaded engine journal bearings [27][28][29][30][31][32][33]. The theoretical results obtained showed that the presence of the couple-stress provides an enhancement in the load carrying capacity, improve the dynamic performance characteristics and the stability of journal bearings, and lengthens the response time of the squeeze film action of the system as compared to the Newtonian lubricant case.…”
Section: Introductionmentioning
confidence: 99%